In vitro performance of Lifetech IBS Angel™ (iron-based bioresorbable scaffold) stents during overdilation for use in pediatric patients - Bjorkman, Kurt; Maldonado, Jennifer R.; Saey, Stephanie; McLennan, Daniel (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To determine what happens with the IBS stent as it is over dilated including the amount of foreshortening and they type of fracturing that occurs. To determine the sheath size needed to safely deliver the stent. Methods: In-vitro testing was performed and repeated for each stent 3 times in temperature-controlled water while imaging in both AP and lateral. This allowed for post testing evaluations Results: A total of 47 stents on monorail system were tested all were pass through either a 4 or 5 French sheath. First strut fracture occurred in both 4 and 6mm stents when they reached 50% larger diameter. Larger stents could achieve 30% increased diameter prior to first strut fracture. No fragments were seen in any stents throughout testing. Conclusion: IBS has thin struts allowing for a lower profile with increased maneuverability and used with smaller sheaths. Embolization of strut fragments with stress testing was not seen. Increased diameter was seen in all with acceptable foreshortening while maintaining radial strength of the lumen.